A Parkinson's disease gene, DJ‐1, repairs brain injury through Sox9 stabilization and astrogliosis. Issue 2 (6th November 2017) - Choi, Dong‐Joo; Eun, Jin‐Hwa; Kim, Byung Gon; Jou, Ilo; Park, Sang Myun; Joe, Eun‐Hye
Abstract: Defects in repair of damaged brain accumulate injury and contribute to slow‐developing neurodegeneration. Here, we report that a deficiency of DJ‐1, a Parkinson's disease (PD) gene, delays repair of brain injury due to destabilization of Sox9, a positive regulator of astrogliosis. Stereotaxic injection of ATP into the brain striatum produces similar size of acute injury in wild‐type and DJ‐1‐knockout (KO) mice. However, recovery of the injury is delayed in KO mice, which is confirmed by 9.4T magnetic resonance imaging and tyrosine hydroxylase immunostaining. DJ‐1 regulates neurite outgrowth from damaged neurons in a non‐cell autonomous manner. In DJ‐1 KO brains and astrocytes, Sox9 protein levels are decreased due to enhanced ubiquitination, resulting in defects in astrogliosis and glial cell‐derived neurotrophic factor/ brain‐derived neurotrophic factor expression in injured brain and astrocytes. These results indicate that DJ‐1 deficiency causes defects in astrocyte‐mediated repair of brain damage, which may contribute to the development of PD. Main Points: A DJ‐1 deficiency decreased Sox9 protein expression in astrocytes by ubiquitination, resulting in defects in astrogliosis and growth factor production, which in turn led to delay in repair of brain injury.